Effects of transient high temperature treatment on the intestinal flora of the silkworm Bombyx mori - Sun, Zhenli (Sci Rep, 2017)
The silkworm Bombyx mori is a poikilotherm and is therefore sensitive to various climatic conditions. The influence of temperature on the intestinal flora and the relationship between the intestinal flora and gene expression in the silkworm remain unknown. In the present study, changes of the intestinal flora at 48, 96 and 144 h following transient high temperature treatment (THTT) of 37 °C for 8 h were investigated. According to principal component analysis, the abundances of Enterococcus and Staphylococcus showed a negative correlation with other dominant genera. After THTT, the gene expression levels of spatzle-1 and dicer-2 were increased and decreased, respectively, which suggested that the Toll and RNAi pathways were activated and suppressed, respectively. The species-gene expression matrix confirmed that the spatzle-1 and dicer-2 gene expression levels were negatively and positively correlated, respectively, with the abundance of Enterococcus and Staphylococcus in the control. The abundance of Variovorax post-THTT was positively correlated with the spatzle-1 gene expression level, whereas the community richness of Enterococcus was negatively correlated with the spatzle-1 gene expression level and positively correlated with the dicer-2. The results of the present investigation provide new evidence for understanding the relationships among THTT, intestinal flora and host gene expression.